The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
1996
DOI: 10.1007/bf01273363
|View full text |Cite
|
Sign up to set email alerts
|

Cholecystokinin peptides and receptor binding in Alzheimer's disease

Abstract: Cholecystokinin (CCK) is a peptide that can be found in the cerebral cortex in high concentrations and is involved in learning and memory as well as neurodegenerative processes. Cortical brain samples from 9 patients with Alzheimer's disease and 9 matched control cases were studied with respect to the concentrations of various molecular forms of CCK and the CCK receptor binding characteristics. No differences were found between patients and controls in any of these measures. Significant correlations were found… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

1996
1996
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 22 publications
0
8
0
Order By: Relevance
“… 38 , 39 , 40 Low levels of CCK are found in AD patient brains and in aged and AD model mice with impaired memory. 22 , 41 , 42 , 43 Here, we found that surgery/anesthesia‐induced cognitive impairment in aged mice, and significantly decreased the levels of CCK‐8 in the hippocampus, especially in CA1 and DG regions. These results indicated that postoperative cognitive impairment was accompanied by a decrease in CCK‐8 levels in the hippocampus, which is consistent with the above‐mentioned reports on cognitive decline.…”
Section: Discussionmentioning
confidence: 59%
See 1 more Smart Citation
“… 38 , 39 , 40 Low levels of CCK are found in AD patient brains and in aged and AD model mice with impaired memory. 22 , 41 , 42 , 43 Here, we found that surgery/anesthesia‐induced cognitive impairment in aged mice, and significantly decreased the levels of CCK‐8 in the hippocampus, especially in CA1 and DG regions. These results indicated that postoperative cognitive impairment was accompanied by a decrease in CCK‐8 levels in the hippocampus, which is consistent with the above‐mentioned reports on cognitive decline.…”
Section: Discussionmentioning
confidence: 59%
“…[38][39][40] Low levels of CCK are found in AD patient brains and in aged and AD model mice with impaired memory. 22,[41][42][43] Here, Synapses are basic information processing units in the brain. 44,45 The correct number and type of synaptic connections are essential for normal CNS functions.…”
Section: Discussionmentioning
confidence: 99%
“…Decreased cholecystokinin within areas such as the prefrontal cortex, amygdala and hippocampus are associated with learning and memory deficits [212]. Cholecystokinin immunoreactivity is decreased in human Alzheimer's disease brain [213] and cholecystokinin analogues prevent cholinergic degeneration in the rat cerebral cortex in an animal model of Alzheimer's disease [214]. Moreover, an age-associated decrease in cortical cholecystokinin concentration may underlie the learning and memory deficits attributable to normal aging in rodents and humans [215,216].…”
Section: Mechanism(s) Of Action Of Angiotensin IV Through Interactionmentioning
confidence: 96%
“…While CCK-B receptor binding does not differ in cognitively normal vs. AD patients (Löfberg, et al, 1996), regional differences in post-mortem CCK concentration suggest an AD-like pattern of decreased expression (Mazurek and Beal, 1991). Thus, we examined if levels of CSF CCK were associated with onset and severity across the AD spectrum, and determined if CCK was related to AD-like changes in cognition, neuroimaging, and classic AD biomarkers like Aβ and tau.…”
Section: Introductionmentioning
confidence: 99%